2012
DOI: 10.1016/j.clinph.2011.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI of sleep spindles and K-complexes

Abstract: Objective Sleep spindles and K-complexes are EEG hallmarks of non-REM sleep. However, the brain regions generating these discharges and the functional connections of their generators to other regions are not fully known. We investigated the neuroanatomical correlates of spindles and K-complexes using simultaneous EEG and fMRI. Methods EEGs recorded during EEG-fMRI studies of 7 individuals were used for fMRI analysis. Higher-level group analyses were performed, and images were thresholded at Z≥2.3. Result f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
65
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 34 publications
28
65
2
1
Order By: Relevance
“…Combined EEG-fMRI studies show that the BOLD correlates of K-complexes comprise multimodal sensory areas as well as key regions in the DMN (e.g., the precuneus) (Caporro et al, 2012; Jahnke et al, 2012) (the resulting activation patterns are shown in Figure 1B), which is consistent with the latter proposed function (brief periods of a “wakefulness-like” brain state).…”
Section: The Global Workpace Theory and Frontoparietal Connectivitysupporting
confidence: 77%
“…Combined EEG-fMRI studies show that the BOLD correlates of K-complexes comprise multimodal sensory areas as well as key regions in the DMN (e.g., the precuneus) (Caporro et al, 2012; Jahnke et al, 2012) (the resulting activation patterns are shown in Figure 1B), which is consistent with the latter proposed function (brief periods of a “wakefulness-like” brain state).…”
Section: The Global Workpace Theory and Frontoparietal Connectivitysupporting
confidence: 77%
“…The three oldest male control subjects have negligible SS densities. These observations suggest that reduced SS density is not specific for PD, in agreement with the fact that many conditions such as cognitive function, memory consolidation, pharmacological interventions and pre-PSG conditions have been reported to influence SS density (De Gennaro and Ferrara, 2003;Caporro et al, 2012). Further analysis including more PD and iRBD patients, together with a more in-depth investigation of cognitive decline and disease severity would be needed to evaluate the relation of abnormalities in SS development in the disease process, and the use of SS as a prognostic marker.…”
Section: Discussionsupporting
confidence: 62%
“…Earlier reports by Peter Halasz and colleagues that KCs express a double nature (Janus-face) (Colrain, 2005; Halász and Bodizs, 2013) are supported by recent fMRI evidence of sensory areas involvement in KCs (Caporro et al, 2012; Jahnke et al, 2012) and even the spontaneous KCs wear at their initial segment the traces of multisensory processing (Riedner et al, 2011). It is thus suggested that “K-complex embodies an arousal with subsequent sleep guarding counteraction that might on one hand serve monitoring of the environment with basic information processing and on the other hand protect continuity of sleep and thus its restoring effect” (Jahnke et al, 2012).…”
Section: Discussionmentioning
confidence: 85%